PAZARLAMADA YAPAY ZEKA UYGULAMALARI: YAPAY ZEKA TEMELLİ LOGO TASARIMLARININ EYE-TRACKING ANALİZİ - AKŞİT, ZEHRA (Fırat Üniveristesi, 2024)
Bu çalışmada, yapay zekâ ve pazarlama ilişkisi ele alınmıştır. Zekâ, günümüzde birçok bilim adamı tarafından tanımlanmaktadır. Ancak bu tanımlar arasında herkes tarafından kabul gören ortak bir tanım bulunmamaktadır. Genel olarak zekâ, canlıları anlama ve kavrama yeteneği ve bu yeteneği kullanabilme kapasitesi olarak tanımlanır. Anlama, çözüm üretebilme, yorumlama, yargılarda bulunma olarak da ifade edilen zekâ, kişisel bilgi ve tecrübelerle ilgilidir. Geçmişten günümüze birçok araştırma ve konusu olan yapay zekâ farklı disiplinlerde de yer almaya başlamıştır. Bu disiplinlerden biri de işletme bilimidir. İşletmeciliğin üretim, insan kaynakları, arge ve pazarlama fonksiyonları açısından da yapay zeka uygulamaları günümüzde de kullanılmaktadır. Makine destekli cihazların insana özgü nitelikleri anlama, çözüm yolu bulma, geçmiş ve gelecek deneyimlerinden fikirler üretme, diğer birimlerle iletişim kurabilme ve üst düzey bilişsel fonksiyonları insan seviyesinde sergileyebilen sistemlerdir. Tıbbı yayınlarda yapay zekâ uygulamalarını kullanabilmek için PubMed veri tabanı uygulamaları kullanılmış ve yıllara göre artış sağlanmıştır. Dijital pazarlama ve yapay zekânın iş birliği, birbiriyle iyi uyum sağlama, verilerle tüketici davranışlarının çevrimiçi etkileşim süreçleri, analitik ve veri sistemlerine dayanmaktadır. Her alanda adından söz ettiren yapay zeka, makine destekli cihazların insana özgü nitelikleri anlama, çözüm yolu bulma, geçmiş ve gelecek deneyimlerinden fikirler üretme, diğer birimlerle iletişim kurabilme, algılama, hatırlama ve üst düzey bilişsel fonksiyonları insan seviyesinde sergileyebilen sistemlerdir. Geçmişten günümüze birçok araştırma konusu olan yapay zekâ farklı disiplinlerde de yer almaya başlamıştır. Tıbbı yayınlarda yapay zekâ uygulamalarını kullanabilmek için PubMed veri tabanı uygulamaları kullanılmış ve yıllara göre artış sağlanmıştır. Bir diğer kullanım alanı ise işletmeciliktir. İşletmeciliğin üretim, insan kaynakları, arge ve pazarlama fonksiyonları açısından da yapay zeka uygulamaları günümüzde de kullanılmaktadır. Pazarlama doğal olarak yapay zekâ uygulamalarından faydalanabilmektedir; metin, görsel, sesli, sanal sistemler, chat botlar, satın alma, yönlendirme ve önerilerdir. Dijital teknoloji sayesinde yüz tanıma, cilt ve vücut şekli tanıma gibi hizmetleri kişiye özel olarak oluşturulan veri tabanlarına aktarabilmektedir. Bu veri tabanlarında kullanılan pazarlama 5.0 uygulamaları yapay zekâ ve pazarlama ilişkisi açısından sıkça kullanılan bir kavramdır. Yapay zekâ, doğal dil işleme, robotik uygulamalar, sanal gerçeklik, bilim gözü ve blok zinciri teknolojik kombinasyonlarının arttığı dönemdir. Pazarlama 5.0 yapay zekâ uygulamalarını mümkün kılan diğer teknolojileri bir araya getirerek müşteriye doğru teklifi sunmaktadır. Büyük veri analizleri kullanılarak müşteriler için kişiselleştirilmiş veri tabanları tek kişilik segmentler şeklinde oluşturulmuştur. Yapay zekâ makineler ve kestirici algoritmalar sayesinde firmaların ürettiği yeni bir ürünün piyasalarda tutup tutmayacağı konusunda ön bilgi sahibi olmaktadırlar. Pazarlama alanında yapay zeka kullanımı, Dijital pazarlama ve yapay zekânın iş birliği, birbiriyle iyi uyum sağlama, verilerle tüketici davranışlarının çevrimiçi etkileşim süreçleri, analitik ve veri sistemlerine dayanır. Pazarlama doğal olarak yapay zekâ uygulamalarından faydalanabilmektedir; metin, görsel, sesli, sanal sistemler, Chat botlar, satın alma, yönlendirme ve önerilerdir. Dijital teknoloji sayesinde yüz tanıma, cilt ve vücut şekli tanıma gibi hizmetleri kişiye özel olarak oluşturulan veri tabanlarına aktarabilmektedir (Kamran, 2021: 40). Yapay zekâ uygulamalarını kullanırken pazarlama açısından Endüstri 5.0 uygulamaları da çok fazla kullanılmaktadır. Yapay zeka;;Siber güvenlik ve savunma sanayi,Sesli asistanlar, Dil çevirileri,Öneri sistemleri,Navigasyon,Sosyal güvenlik,Sağlık hizmetleri, e-Ticaret ve yardımcı robot uygulamalarıyla günlük hayatımızda yer almaktadır. Siber güvenlik ve savunma sanayi gibi sektöre özel stratejik çalışmalarda da kullanılmaktadır.

In this study, the relationship between artificial intelligence and marketing is discussed. Intelligence is defined by many scientists today. However, there is no common definition accepted by everyone among these definitions. In general, intelligence is defined as the ability to understand and comprehend living things and the capacity to use this ability. Intelligence, which is also expressed as understanding, generating solutions, interpreting and making judgments, is related to personal knowledge and experience. Artificial intelligence, which has been the subject of many researches and topics from past to present, has started to take place in different disciplines. One of these disciplines is business science. Artificial intelligence applications are also used today in terms of production, human resources, R&D and marketing functions of business administration. Machine-aided devices are systems that can understand human-specific qualities, find solutions, generate ideas from past and future experiences, communicate with other units and exhibit high-level cognitive functions at human level. PubMed database applications have been used to use artificial intelligence applications in medical publications and an increase has been achieved over the years. The collaboration of digital marketing and artificial intelligence is based on the collaboration of digital marketing and artificial intelligence, adaptation to each other, online interaction processes of consumer behavior with data, analytics and data systems. Artificial intelligence, which has made a name for itself in every field, is the systems that can exhibit machine-supported devices' human-specific qualities such as understanding, finding solutions, generating ideas from past and future experiences, communicating with other units, perceiving, remembering and high-level cognitive functions at human level. Artificial intelligence, which has been the subject of many researches from past to present, has started to take place in different disciplines. PubMed database applications have been used to use artificial intelligence applications in medical publications and an increase has been achieved over the years. Another area of use is business administration. Artificial intelligence applications are also used today in terms of production, human resources, R&D and marketing functions of business administration. Marketing can naturally benefit from artificial intelligence applications; text, visual, audio, virtual systems, chat bots, purchasing, referrals and recommendations. Thanks to digital technology, services such as face recognition, skin and body shape recognition can be transferred to personalized databases. Marketing 5.0 applications used in these databases is a frequently used concept in terms of the relationship between artificial intelligence and marketing. This is the period in which technological combinations of artificial intelligence, natural language processing, robotic applications, virtual reality, science eye and blockchain are increasing. Marketing 5.0 offers the right offer to the customer by bringing together other technologies that enable artificial intelligence applications. Using big data analytics, personalized databases for customers are created in the form of single segments. Thanks to artificial intelligence machines and predictive algorithms, companies have prior knowledge about whether a new product will catch on in the markets or not. The use of artificial intelligence in the field of marketing is based on the collaboration of digital marketing and artificial intelligence, the ability to adapt well with each other, the online interaction processes of consumer behavior with data, analytics and data systems. Marketing can naturally benefit from artificial intelligence applications; text, visual, audio, virtual systems, chat bots, purchasing, referrals and recommendations. Thanks to digital technology, it can transfer services such as face recognition, skin and body shape recognition to databases created specifically for individuals (Kamran, 2021: 40). While using artificial intelligence applications, Industry 5.0 applications are also used a lot in terms of marketing. Artificial intelligence; Cyber security and defense industry, Voice assistants, Language translations, Suggestion systems, Navigation, Social security, Health services, e-Commerce and assistant robot applications are in our daily lives. It is also used in sector-specific strategic studies such as cyber security and defense industry. The intrinsic value of the study was determined in 3 dimensions. In the economic dimension, based on the results of studies such as PwC's (PricewaterhouseCoopers is a multinational professional services network headquartered in London, United Kingdom and operating as partnerships under the PwC brand) 'Artificial Intelligence Study' and McKinsey's 'Modeling the global economic impact of artificial intelligence', the contribution of artificial intelligence to the global economy is expected to rise to $15.7 trillion by 2030, with an economic output of over $13 trillion. However, it is stated that productive AI could contribute "between 2.6 trillion and 4.4 trillion dollars annually" to the global economy, which is close to the economic equivalent of adding a new country the size and productivity of the United Kingdom to the world. Industrial production, logistics and supply chains powered by AI make it possible for businesses to be more competitive in the international arena and thus companies have the opportunity to increase their exports. In this context, integrating the economic outputs of the applications of artificial intelligence in the field of marketing to the firms in Elazığ will make a significant economic and social contribution. In terms of contribution to the literature; the literature on the subject is still new in Turkey, and for this reason, it is not possible to conduct research since there is no scale. The subject has been examined theoretically in a small number. There is no research on these issues in the Higher Education Council Thesis. Since there is no theoretical study that examines the subject in a theoretically broad way, the study will be examined theoretically in all its aspects. With the dimension of social contribution; It will be examined within the scope of artificial intelligence how the application of getir, a company that offers delivery services for restaurant food deliveries and grocery products through its mobile application established in 2015, works in the field of marketing. For this purpose, for the application of GETIR company in Elazığ, the owner of the company will be interviewed and the functioning of the system will be discussed through in-depth interviews. It is aimed to determine the possible contributions of the results obtained to the companies operating in various sectors in Elazig and their current situation in terms of artificial intelligence applications and to share the economic performance of the companies with the owners of the companies with the potential for application and to be completed in about 12 months.
Artificial intelligence applications in marketing: Eye-tracking analysis of artificial intelligence based logo designs
Keywords: İşletme